Jerusalem within these walls (Pittsburg : National Geographic Society, 1986)
Jerusalem's old city is a tiny enclave where some of history's greatest dramas have been enacted. Busy and colorful, it is the fountainhead of three major religions, the site of many of the world's most venerated shrines, and home to 26,000 people of profoundly different cultures who live side by side in a fragile peace.
APD 2419